2018
DOI: 10.1002/smtd.201800056
|View full text |Cite
|
Sign up to set email alerts
|

3D Current Collectors for Lithium‐Ion Batteries: A Topical Review

Abstract: Current collectors play important roles in enhancing the electrochemical performance of lithium‐ion batteries. Currently used collectors are mostly made of aluminum or copper foils through slurry casting with binders that have not reached optimal capacity. Furthermore, extended cycles of charge and discharge induce detachment of the cast layer, resulting in damage to the structural integrity. In order to better understand the principles of the performance of and thus optimize current collectors, a critical rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(94 citation statements)
references
References 141 publications
(140 reference statements)
1
93
0
Order By: Relevance
“…For instance, Zhu et al demonstrated the wavelength‐tunable lasing from MAPbX 3 nanowires with pretty low lasing threshold (220 nJ cm −2 ) . Some closely related works of discussing the exciton photophysics and exciton lasing can refer to the reviews . Note that, besides the commonly studied photonic lasing, exciton–polariton lasers have also been realized by employing perovskite materials as discussed in Section .…”
Section: Photogenerated Free Charge Carrier: Transport Recombinationmentioning
confidence: 99%
“…For instance, Zhu et al demonstrated the wavelength‐tunable lasing from MAPbX 3 nanowires with pretty low lasing threshold (220 nJ cm −2 ) . Some closely related works of discussing the exciton photophysics and exciton lasing can refer to the reviews . Note that, besides the commonly studied photonic lasing, exciton–polariton lasers have also been realized by employing perovskite materials as discussed in Section .…”
Section: Photogenerated Free Charge Carrier: Transport Recombinationmentioning
confidence: 99%
“…[133][134][135] Hierarchical micro-nanostructured electrodes can exploit the positive attributes of nanostructures for increased surface area, nanometer diffusion lengths, nano-confinement effects, and microstructures for improved stability and ease of handling during electrode preparation. 119,136 They can be fabricated through the aggregation of nanosized crystallites to form larger, porous agglomerates, which can be then further grouped into micrometer-sized grains (e.g., see Fig. 5).…”
Section: Electrode Morphology and Structuringmentioning
confidence: 99%
“…Therefore, new nanostructuration strategies have been developed to address these above challenging issues. Particularly, nanoarchitectured current collectors thus have emerged as one of the most efficient strategies . In this section, we will first give introductory background on the charge storage mechanisms of pseudocapacitive materials, and then outline the subsequent design considerations of ideal nanoarchitectured current collectors for PCs.…”
Section: Design Philosophy Of Nanoarchitectured Current Collectors Fomentioning
confidence: 99%